Restored inner dome - Ghosh, Ayan (Jio Institute, 2023)
The inner dome is located at a height of 90 feet from the ground. In recent times, the inner dome has been beautifully restored as part of ongoing conservation efforts. Other than structural restoration, the dome has been painted and special lighting has been installed for daytime illumination.